Tissue Factor Expression in Colorectal Adenocarcinoma: Association with Angiogenesis and Clinical and Pathological Aspects - Fillmann,Lúcio Sarubbi (2022)
Abstract Introduction Tissue factor (TF) expression has been described in various neoplasms and was correlated with angiogenesis and metastases. Objectives To describe TF expression in colorectal cancers, correlating it with microvessel density and clinical and pathological variables. Methods Immunohistochemistry was used to determine TF expression and microvessel density. The Student t-test was used to compare high and low TF expression with microvessel density andwith age. The chi-squared test was used for other comparisons, and Kaplan-Meier curves were used for survival analyses. Results Forty-three patients were operated with curative intent. Their mean age was 58.1±12.6 years old, and 62.8% were male. The rectum was the most common location (60,4%), and most tumors reached the serosa and peri-intestinal fat (72.1%). Lymph nodes were positive in 46.5%, and 72.1% of the tumors were moderately differentiated adenocarcinomas. Death occurred in 27.6±12.8months in 51.1% of the patients who had recurrence. Tissue factor expression was intense in 88.4%. There was a positive correlation between TF expression and microvessel density (p=0.02), and between TF and older age (p<0.01). There was no correlation between TF expression and other variables (gender, histological type, penetration into the intestinal wall, and lymphatic and systemic metastases). Tissue factor expression did not correlate with survival. Conclusion Tissue factor expression correlated with increased microvessel density and older age. Further studies are necessary to ascertain the clinical relevance of TF in colorectal cancer.